SHARIA FINANCIAL LITERACY OF NUTMEG FARMERS IN BANDA ISLANDS - Ramadhan Fitrah Faris; Yayat Sujatna (Universitas Brawijaya, 2023)
It should be noted that according to the results of the OJK SNLIK in 2021, the level of Islamic financial literacy is 8.93%; this figure is certainly below the survey was corroborated by Indonesia's high literacy rate of 21.84%. The low literacy of Indonesian Islamic finance based on OJK data in 2020 was also contributed by Maluku Province, which has a very low level of Islamic financial literacy of only 2.9%. This figure is only higher than NTT, West Sulawesi, and Papua and far behind North Maluku, which reached 12.73%. The low literacy of Islamic finance in Maluku synergizes with the low level of financial literacy, which is only 36.48 percent. This figure is lower than the country's overall literacy rate of 38.03 percent. This study uses the MIX Method, or mixed research. The results of the research based on the survey found that Islamic financial literacy in the Banda sub-district is at a moderate rate, namely 60%. Based on interviews, it was found that there were 11 factors that hindered Islamic financial literacy, namely: Language, Assumptions, lack of curiosity, unavailability of infrastructure, culture, transaction needs, digital capability, willingness to Learn, Environment, Poverty Level, and low education level. And also found 7 solutions, namely: Behavior Modification, Willingness to Ask, Technology and Information, Knowledge and Decisions, Socialization and Education, Government Funding Programs, and government and universities. This research will have a positive impact on the welfare of nutmeg farmers if applied in real life.